Optimization of the color fastness and mechanical properties of pigment dyed PC fabric. Issue 5 (10th August 2018) - Azeem, Abdul; Abid, Sharjeel; Sarwar, Noman; Ali, Shahzaib; Maqsood, Ahsan; Masood, Rashid; Hussain, Tanveer
Abstract : Purpose: The purpose of this study is to improve the mechanical properties and reduce the stiffness/harshness of fabric associated with the pigment dyeing of textiles. Design/methodology/approach: The fabric was pigment dyed with the addition of three different softeners and binders. The fabric was then analyzed to have improved textile properties by measuring tear strength, bending length, crocking and washing fastness tests. Findings: The conventional route of pigment dyeing (without any softener) imparted poor mechanical and rubbing fastness. The softener-added recipe provided better mechanical, rubbing and washing fastness, and the stiffness values were oppressed as well. Practical implications: Because of reduced stiffness, increased fastness and mechanical properties, the use of softener with pigment dyeing can improve the market values and satisfaction of the dyed fabrics. The finished product would also have better life and endurance. The process can be modified easily to have a better end-product with a negligible cost addition in industrial process, as softeners are cheap and used in low (10-20 g/l) in industrial settings without affecting the required shades. Originality/value: This is the first report, to the best of the author's knowledge, on the optimization of pigment dyeing of PC fabric with the addition of Helizarin and perapret softeners in dyeing bath.